The times they are a-changin: implementing new psychiatric rehabilitation models within a community care in the post COVID-19 era.: New post-COVID rehabilitation models - Pelizza, Lorenzo; Pupo, Simona (Acta Biomedica Atenei Parmensis, 2021)
During the COVID-19 pandemic, community healthcare treatments have played a crucial role in early detection and intervention against the epidemic spreading (as most of the infected individuals were at home). For the national policy on mental health services in Italy, “the person as a community resource within a caring community” is still a crucial idea that the COVID-19 era helped to revive, together with the supremacy of the public healthcare pathway over the private one. In this article, new mental health rehabilitation models (such as the Personal Health Budget and the Individual Placement and Support) are suggested as useful intervention approaches on which to base psychiatric care within a community care in the post COVID-19 era.